2018
DOI: 10.1055/a-0574-3166
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Phase Angle and Handgrip Strength Induced by Suspension Training in Older Women

Abstract: This study aimed to present a suspension exercise training program suitable for older adults and to verify the effect of 12 weeks of training on handgrip strength (HS) and anthropometric and bioelectrical impedance parameters in older adults. Thirty older women (age 66.1±4.7 years, BMI 30.6±5.3 kg/m) were randomly assigned to one of two groups: a training group (TG, n=15) or a control group (CG, n=15). The TG participated in a 12-week suspension training program, while the CG maintained their normal physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 31 publications
4
56
1
1
Order By: Relevance
“…Pre = Pre-intervention period, Post = Post-intervention period. Campa et al [8], and we agree with them when they suggest that this may be considered to be a consequence of constantly having to grab the handles of the suspension training system. Similar increases in grip strength after a HIIT training period were highlighted by Onambelé et al [46], when comparing their results with those of a control group and by García-Pinillos et al [15], which showed a significant increase in grip strength after HIIT.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Pre = Pre-intervention period, Post = Post-intervention period. Campa et al [8], and we agree with them when they suggest that this may be considered to be a consequence of constantly having to grab the handles of the suspension training system. Similar increases in grip strength after a HIIT training period were highlighted by Onambelé et al [46], when comparing their results with those of a control group and by García-Pinillos et al [15], which showed a significant increase in grip strength after HIIT.…”
Section: Discussionsupporting
confidence: 85%
“…However Ramirez et al [50], in a study with the same intensity of HIIT and the same duration of intervention did not find significant improvements in waist and hip circumference in adults with metabolic syndrome and Bartlett et al [5], in a recent study involving elderly people over 64 years, described no significant improvement in fat percentage after 10 weeks of HIIT intervention. On the other hand, very few studies have analyzed the effects of suspension training, especially in older adults, and thus a recent study performed on older women (aged 66.1 ± 4.7 years) showed that a 12-week suspension exercise training program led to significant decrease in percentage of fat mass, as well as in triceps, biceps and subscapular skinfolds [8].…”
Section: Discussionmentioning
confidence: 99%
“…Bioelectrical impedance analysis (BIA) has been widely used as a rapid, safe and non-invasive method for monitoring active adults performing recreational exercise and elite athletes [4][5][6] and in estimating body composition and nutritional status in healthy non-athletes and adults with clinical conditions [7][8][9]. Alternating current is introduced into the body by bioimpedance electronic devices at single or multiple frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The ICW/ECW ratio is identified by the bioelectrical phase angle (PA), which is calculated as the arctangent of Xc/R × 180 • /π [5][6][7]. An increase in ICW/ECW can be a consequence of gain in muscle mass due to physical activity [8][9][10][11]. However, the analysis of only the PA leads to interpretation errors.…”
Section: Introductionmentioning
confidence: 99%